REASONS FOR THE DEVELOPMENT OF AUTISM FROM THE POINT OF VIEW OF THE METHOD OF PSYCHOTHERAPY «I-RECONSTRUCTION» - Pavlenko, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines definitions and existing views on understanding the causes of autism and provides a completely new perspective on this problem. In particular, a new understanding of the concept of «acquired autism» is proposed, the role of the preverbal period in the development of symptoms is highlighted, and the direction of work with clients is suggested.